Does behaviour affect the dispersal of flatback post-hatchlings in the Great Barrier Reef?. Issue 5 (24th May 2017) - Wildermann, Natalie; Critchell, Kay; Fuentes, Mariana M. P. B.; Limpus, Colin J.; Wolanski, Eric; Hamann, Mark
Abstract : The ability of individuals to actively control their movements, especially during the early life stages, can significantly influence the distribution of their population. Most marine turtle species develop oceanic foraging habitats during different life stages. However, flatback turtles ( Natator depressus ) are endemic to Australia and are the only marine turtle species with an exclusive neritic development. To explain the lack of oceanic dispersal of this species, we predicted the dispersal of post-hatchlings in the Great Barrier Reef (GBR), Australia, using oceanographic advection-dispersal models. We included directional swimming in our models and calibrated them against the observed distribution of post-hatchling and adult turtles. We simulated the dispersal of green and loggerhead turtles since they also breed in the same region. Our study suggests that the neritic distribution of flatback post-hatchlings is favoured by the inshore distribution of nesting beaches, the local water circulation and directional swimming during their early dispersal. This combination of factors is important because, under the conditions tested, if flatback post-hatchlings were entirely passively transported, they would be advected into oceanic habitats after 40 days. Our results reinforce the importance of oceanography and directional swimming in the early life stages and their influence on the distribution of a marine turtle species.